Automation of aristotelian syllogistic. Logical and phenomenological foundations of the automaton “Syllogismos” - Vargas Guillén, Germán (Estudios de Filosofía, 2002)
The objective of this article is to show the foundations of the research in which the device Syllogismos have been developed, an automaton (hat: performs inference, identifies the figure and the mode of syllogisms, recognizes and differentiates enthymeme and sophisms; this was developed in Prolog -a platform of Artificial Intelligence (Al)- as pari of a research project tending to represent computationally the mind just as Aristotle conceived it for the case of logic in Organon, for the case of persuasion in Rhetoric, etc. In § 1. the research context is presented: in § 2. the contribution of syllogistics to Al is characterized as well as to the philosophy of the mind: in § 3. the limitations of Aristotelian logic are established for its automation: in f 4. it studies the perspective of research opened with automation projects